Prefix SISTEM PENGISIAN AIR PADA TANKI PEMBUATAN ROTI DENGAN METODE FUZZY LOGIC MENGGUNAKAN ARDUINO - Ghaleb, Mohammad Ghaleb Ahda (Universitas Islam Balitar Blitar, 2023)
The filling of water as a composition in making bread dough manually often has a very significant error in the amount of water volume. Therefore, filling water as a composition of bread dough automatically reduces the excess amount of water volume during bread dough making. With automatic water filling in bread dough making, the volume of water is within the tolerable amount so that the dough is quite good and makes the time efficiency of making bread dough compared to filling water as bread dough manually.